EFEKTIVITAS PEMANFAATAN SIMANTAP P2S3 DALAM PENGELOLAAN KEUANGAN SANTRI SALAFIYAH SYAFI'IYAH SUKOREJO: PENDEKATAN BERBASIS KONSUMEN - Asmito, Asmito; Rafik, Zainur (Al-Idarah, 2023)
One of the 17 goals of sustainable development is infrastructure innovation for all social structures of society, including the education sector. Pondok Pesantren Salafiyah Syafi'iyah Sukorejo Situbondo as a stakeholder of the SDGs has attempted to launch a new innovation in conducting education fee transactions known as Sistem Manajemen Uang Tahunan Pondok Pesantren (SIMANTAP) or the Annual Islamic Boarding School Money Management System. Based on the theory of the technology accepted model, perceived convenience and perceived usefulness affect the acceptability of a technological innovation. This study aims to measure the effectiveness of the use of SIMANTAP in the financial management of the students of Salafiyah Syafi'iyah Sukorejo Situbondo from a consumer perspective. Data was collected through a closed questionnaire from 50 santri guardians who were present or attend at the commemoration of the Prophet Muhammad's birthday. Then the data obtained will be analyzed descriptively. The seven dimensions used in this study resulted that the ratio of voluntary effectiveness reached 80.5%, complexity reached 48.5%, trial reached 78%, impression reached 75.5%, job relevance reached 85.5%, attitude towards work reached 76% and accessibility reached 83%.